Electrical and Magnetic Properties of Si Ion Implanted Yba 2cu3o7-? Thin Films and Microbridges - Avcı, İlbeyi; Tepe, Mustafa; Abukay, Doğan; Serincan, Uğur; Öktem, Bülent; Turan, Raşit; Abukay, Doğan (Elsevier Ltd., 2004)
Fabrication of superconducting bilayer YBa2Cu3O 7-δ (YBCO) thin film structure by Si ion implantation and properties of microbridge patterned on that are presented. YBCO thin film of 150 nm thickness was grown on single crystal (100) SrTiO3 substrate by inverted cylindrical magnetron sputtering. The sample was implanted with 100 keV, 1×1016 Si ions/cm2. Upon implantation with Si, the sample lost its electrical conductivity and diamagnetism while its crystalline structure was preserved after the annealing of the sample. The implanted ions do not alter the overall crystal structure of high temperature superconductor film. This allows the growth of epitaxial superconducting second layer YBCO film on top of the implanted area without using any buffer layer, thus providing an effective method of fabricating multilayer structures. The second layer film and the microbridge patterned by laser writing technique, showed the superconducting properties similar to those of pure YBCO base layer with a reduced critical current density.
Keywords: Ion implantation; Multilayers; Thin films; Laser writing; Microbridges; Plasma power